2019
DOI: 10.1136/bmjopen-2018-027012
|View full text |Cite
|
Sign up to set email alerts
|

What is the contribution of physician associates in hospital care in England? A mixed methods, multiple case study

Abstract: ObjectivesTo investigate the deployment of physician associates (PAs); the factors supporting and inhibiting their employment and their contribution and impact on patients’ experience and outcomes and the organisation of services.DesignMixed methods within a case study design, using interviews, observations, work diaries and documentary analysis.SettingSix acute care hospitals in three regions of England in 2016–2017.Participants43 PAs, 77 other health professionals, 28 managers, 28 patients and relatives.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 20 publications
4
59
0
Order By: Relevance
“…Recent research has shown that PAs were found to be acceptable, appropriate and safe members of the medical and surgical teams by the majority of doctors, managers and nurses. 13 Forty-three PAs, 77 other healthcare professionals, 28 managers, and 28 patients and relatives participated in the study. The results showed that PAs were mainly deployed to undertake inpatient ward work in the medical/ surgical team during core weekday hours.…”
Section: How Pas Can Work In Medical Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that PAs were found to be acceptable, appropriate and safe members of the medical and surgical teams by the majority of doctors, managers and nurses. 13 Forty-three PAs, 77 other healthcare professionals, 28 managers, and 28 patients and relatives participated in the study. The results showed that PAs were mainly deployed to undertake inpatient ward work in the medical/ surgical team during core weekday hours.…”
Section: How Pas Can Work In Medical Teamsmentioning
confidence: 99%
“…They were reported to positively contribute to continuity within their medical/surgical team, patient experience and flow, inducting new junior doctors and supporting the medical/surgical teams' workload, which released doctors for more complex patients and their training. 13 Physician associates (PAs) are a relatively new medical professional group working as part of the multidisciplinary team to deliver patient care. This article aims to look at how PAs can work effectively in teams, highlighting the benefits and current working practices of PAs across the NHS and address the concerns and challenges raised.…”
Section: How Pas Can Work In Medical Teamsmentioning
confidence: 99%
“…As described in other literature, individual PAs roles are described as mouldable, which allows the PA to work across silos within the organization in order to fill the needs of their setting. Working across these barriers enables PAs to address care delivery gaps, provide continuity, increase collaborative care, enhance communication, aid patient flow, enhance care during transitions, and free up physician time for other patients or activities (4,27,28). Most importantly, PAs contribute to a relationship infrastructure that enables effective communication between patients and their health care team.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies echo the importance of determining the appropriate level of regulation and funding support to fully realize the utility of PAs and to optimize their integration (4,7). In addition, the lack of policy around reimbursement and incentives means that existing payment incentive mechanisms and the legacies of past policies are driving various stakeholders to pursue divergent interests (i.e.…”
Section: Recommendations For Practice Policy and Researchmentioning
confidence: 99%
“…Physician Assistants (PAs) are advanced clinical practitioners trained in the medical model to extend physician services, and are currently employed in a wide variety of healthcare settings across a number of countries, including the United States, United Kingdom, Australia, and the Netherlands (1)(2)(3). The role of PAs may offer solutions to the inherent tensions between service demands, training requirements and budgetary restraints, compensate for cyclical health workforce shortages, provide a flexible addition to the healthcare workforce, provide team continuity, and improve patient experiences (4)(5)(6)(7). Hoping to achieve similar results in Ontario (Canada), the Ontario Ministry of Health and Long Term Care introduced PAs in 2006 as a potential health human resource innovation to improve access to care, reduce wait times, and support the complex needs of healthcare delivery in Ontario (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%